CODESRIA Bulletin Online, No. 9, March 2022 - In the Shadows of the Natural Sciences: The Humanities in Crisis or the Crisis of Humanity ? - Nasong’o, Wanjala Sandrack (CODESRIA Bulletin, 2022)
Introduction The sociology of knowledge categorises the fields of intellectual inquiry into the humanities, natural sciences, and social sciences. The natural sciences study natural phenomena using empirical evidence from observation and experimentation with a view to not only describing and understanding such phenomena, but also predicting the same. They are divided into life sciences (botany and zoology), physical sciences (astronomy, chemistry, and physics), and earth sciences (geology, oceanography, meteorology, and palaeontology). The humanities are broadly defined as a large family of disciplines that study the expressions of the human mind. They include the study of languages and cultures, literature and the fine arts, musicology, history and archaeology, religions, ethics, gender, and philosophy, in their widely ranging forms, including important sections of communication and media studies (Vale 2011: 22–3). Social sciences on the other hand, are the disciplines that fall between the humanities and natural sciences. They include anthropology, economics, geography, political science, psychology, and sociology among others. The taxonomic distinction between the humanities and social sciences is said to be a conceptual distinction between two forms of knowledge which are, erroneously some would say, seen as abstract (humanities) and applied (social sciences). Social sciences’ claim to applied knowledge rests on the argument that traditionally, social science disciplines often focus on defining social problems and intervening in their solution while the humanities are said to focus mainly on hermeneutics, i.e., interpretation and understanding. According to Bod and Kursell (2015: 338), the humanities study texts, they study the products of human culture, but in this they are ‘typically distinguished from the social sciences in having a significant historical element, in the use of interpretation of texts and artefacts rather than experimental and quantitative methods, and in having an idiographic rather than nomothetic character’. Ideographic approaches, prevalent in the humanities, emphasise the unique elements of individual social phenomena, the historically particular, and are thus individualising approaches. Nomothetic approaches prevalent in the social sciences, however, focus on providing general law-like conclusions about social phenomena, they seek to emulate the scientific logic and quantitative methodology of the natural sciences. They thus seek to produce generalising rather than individualising epistemologies. Despite the presumed taxonomic difference between the humanities and social sciences, however, juxtaposed with the natural sciences, they are ontologically similar in their focus on social phenomena in contradistinction to natural sciences which focus on the physical world. The natural sciences, such as astronomy, biology, chemistry, geology and physics employ strictly quantitative methods, experimental research, and both deductive and inductive scientific logic to describe, explain, and predict natural phenomena as well as make prescriptions about them. They generate the quintessential applied knowledge. Indeed, the utilitarian value of their knowledge products in areas such as medicine, engineering, computing and mechanics has elevated them to the pride of place both in the academy and in society generally. Conversely, the utilitarian relevance of the humanities and social sciences has increasingly been questioned, especially in the contemporary neoliberal global dispensation given its free-market logic and quest for profit maximisation. In this paper, I examine the current crisis within the humanities with a view to explicating its causal factors and proffering possible remedies. I argue, like some critical voices in the academy have done, that the crisis in the humanities is essentially reflective of a crisis within humanity more generally. The Crisis in the Humanities and its Causes According to Ibanga Ikpe (2015: 50), the debate as to whether the humanities are in decline is almost over. Statistics on declining enrolments, shrinking job prospects, dwindling funding, and growing condescension from society add up to show that all is not well. He notes that the future of the humanities as an academic pursuit that is relevant to the needs of society has been variously described as gloomy, hopeless, and bleak. This diagnosis has been mainly due to declining interest in the humanities both by students and the society in general. Whereas the more favoured disciplines in the natural sciences, especially in the science, engineering, and technology subfields bask in the admiration of society and thereby attract funding for studies, research and community engagements, the humanities disciplines continually struggle under the threat of being consigned, like alchemy, to the dumpsite of historical relics. Indeed, whereas students fight to be accepted into any one of the favoured natural science or business programmes, and such programmes can pick and choose from among the best of students, students for the most part only consider the humanities as a last resort. Consequently, humanities departments have to settle for students that have been rejected by other programs (Ikpe 2015: 51). The reason for this sorry state of affairs is not farfetched, according to Ikpe – the humanities are said to have failed to evolve with society and have therefore lost relevance. Courses in the humanities are generally seen as belonging to a long past era when there was no need for specialised skills for entry into the technical areas of the marketplace. According to Ikpe (2015: 52), although there is no consensus as to when the decline of the humanities and social sciences began, the decline may have accelerated in recent times but it is not a recent phenomenon. Some scholars link the decline to the continuing current of positivism within the Western academy. Positivism defined quantity as the measure of reality and, in doing so, devalued the traditional knowledge of the public relevance of a liberal education (Frodeman et al. 2003). Other scholars trace the decline to the liberationist climate of the 1960s (Deneen 2010) and the desire of the youth to free themselves from the constraining academic culture of the humanities. Yet other scholars go so far as identifying the decline of the humanities with the founding of the American university and its links with the fortunes of the entrepreneurial class. As Newfield (2003) argues, the liberal arts tradition and the capitalist culture are contradictory forces that create conflicts for both the academy and the students who go on to constitute much of the middle class. From a philosophical perspective, the decline in the humanities is sometimes attributed to the school of W.V.O. Quine, which espouses what Ikpe refers to as ‘scientism’. This is the perspective that the best of our knowledge-claims are the ones advanced by scientists (see Meynell 2010: 976). This philosophy and the increasing interaction of humanity with the products of science is viewed as having laid the foundation for an eclipse of the humanities, despite centuries of the humanities being at the centre of intellectual discourse. Others see it as having a much longer history and trace it to Francis Bacon’s volume published in Latin, Novum Organum and its view that learning should consist of a careful study of nature rather than the analysis of ancient texts. David Hume is said to have also contributed to the eventual decline of the humanities in his rejection of metaphysics. He argued: If we take in our hand any volume; of divinity or school metaphysics, for instance; let us ask, does it contain any abstract reasoning concerning quality or number? No. Does it contain any experimental reasoning concerning matter of fact and existence? No. Commit it then to the flames: for it can contain nothing but sophistry and illusion (Hume [1748] 1984: 149). Hume’s influence and the subsequent rise in positivism, especially Auguste Comte’s suggestion that all real knowledge should be derived from human observation of objective reality, ‘vindicated the statements of common-sense fact and of science, but stigmatized those of metaphysics and religion as meaningless or nonsensical’ (Meynell 2010: 975). Similarly, Immanuel Kant’s distinction between the higher and lower faculties and his view that the ‘higher faculties’ of medicine and law should be rated higher than the ‘lower faculties’ of theology and philosophy was arguably an early sign of the decline of the humanities. Such views heightened scepticism concerning knowledge from the humanities, especially since such knowledge is seen not to have any immediately visible practical application in society. More recent intellectual discourse blames the decline of the humanities on the corporatisation of universities. Donoghue (2008) for instance, attributes the decline of the humanities to the infiltration of market forces into the administration of universities, especially the fact that economic motivations rather than academic concerns have become the basic foundation for decision making in the academy. Bill Readings (1997) advances this argument in his appropriately titled book, The University in Ruins. He contends that the increasing globalisation of capital is undermining the nation-state and with it the national cultures that have been the university’s integrating principle since the Enlightenment (see also, Sirluck 1997: 617). As has already been said, Newfield (2003) argues that the liberal arts tradition and capitalist culture are contradictory forces that create conflicts for both the academy and students. This explains why university corporatisation cannot exist side by side with a thriving humanities culture (see Clark 2008: 467). Donoghue sees the intervention of market forces in academia as giving rise to ‘for profit’ universities and the tendency to de-emphasise the humanities and any such disciplines that cannot be ‘granularised’ into formulaic information bits. The result is best illustrated by Donoghue’s quotation of John Sperling, leader of the for-profit education movement and founder of the University of Phoenix when he says, ‘we are not trying to develop value systems or go in for that “expand their minds” bullshit’ (Donoghue 2008: 97). Donoghue argues that it is the success of such business-oriented institutions in providing cheaper, market-defined and more flexible education that puts pressure on others to adopt ‘for-profit’ strategies in an attempt to survive in an increasingly competitive industry. As Weisbuch (1999: B4) rightly argues, whether the decline is due to a chain of contemporary events or due to a philosophical theory of an immediate or distant past, there is no denying the fact that the humanities, like the liberal arts generally, appear far less surely at the centre of higher education than it once did, and has lost the respect of colleagues in other fields as well as the attention of the general public. In the case of Kenya, nothing captures this reality better than the pronouncements of Deputy President William Ruto on the same. Addressing the press shortly after defending his PhD thesis in human ecology on 24 October 2018, Ruto dismissed anthropology, geography, history, and sociology as courses not worthy studying at the university. Urging universities that receive public funding to ‘up their game’, Ruto asserted that universities should be ashamed of churning out ‘unemployable’ graduates who end up ‘roasting maize on the roadside’ (Nasong’o 2018). In his view, universities should only teach the natural sciences and technical courses that guarantee employment post-graduation. Ruto similarly dismissed the arts and humanities in 2010 while serving as minister for higher education (Njoya 2010). This dismissal of and disdain for the humanities both in Kenya and elsewhere is, in fact, reflective of a profound crisis in humanity more generally. The Crisis in Humanities as a Crisis of Humanity It is eminently evident that the crisis in the humanities is indeed reflective of a fundamental crisis in humanity as a whole. This is manifested at four different levels: (1) the tyranny of passion, or the rule of the senses; (2) the demands of market forces and the worship of materialism; (3) the mantra of privatisation and preoccupation with the bottom line; and (4) complicit humanities scholars. In other words, the decline of the disciplines of the humanities is a function of the decline of society itself. As Ikpe (2015) rightly argues, although the decline of the humanities is often seen as an isolated crisis, it is in fact indicative of a wider crisis within humanity, and to a great extent, it is nothing compared to the parallel crisis within humanity. This is because, in his view, the crisis in the humanities could be said to be temporary and can be resolved either through a reinvention which creates a new niche within society for the humanities or when the current humanities scholars are led by some divine intervention to undergo some transformative Pauline experience and change the course and fortunes of humanities scholarship. The crisis within humanity on the other hand is a lot more complex and can neither be phased out nor resolved through reinvention. It is a crisis that threatens the essence of humanity as we know it and with it several centuries of human civilisation. The crisis in humanity threatens to redefine what it means to be human and at the same time create the nightmarish scenario of complete human extinction or mutation. It is a crisis which is not always recognised for the interrelated colossus that it is but is sometimes treated as isolated events that could be resolved with targeted interventions. It is a crisis which all the resources of human knowledge and wisdom should be utilised as far as possible in providing basic diagnoses and indicating directions of resolution (Bidney 1946: 534). But what is the nature of this crisis and to what extent should humanity feel threatened by it? Let us examine the four levels of this crisis in humanity more closely. The Tyranny of Passion, or the Rule of the Senses The tyranny of passion or the rule of the senses is related to what Ibanga Ikpe (2015) calls the seduction by the fleshpots of consumerism. This seduction, so prevalent in contemporary society, has resulted in an unhealthy desire for things that titillate the senses and that enflame the passions, thus leading to a decline in the desire for things intellectual and moral-ethical, the fulcrum of the essence of the humanities. It is this tyranny of passion that has led to contemporary society’s preoccupation with the celebrity culture, the sponsor-sponsee transactional relationships, the slay queen-slay king phenomenon, the transient Facebook/ Meta and Instagram likes and dislikes; and the concomitant dislike and denigration of everything that does not lead to immediate gratification. In discussing the crisis within humanity, Huxley (1949: 199) observes that it exists, so to speak, on two levels: an upper level of political and economic crisis and a lower-level crisis in population and world resources. The lower-level crisis of humanity flows from the rapidly growing population of the world, which far outstrips the growth in food production and the capacity of the world economy to provide meaningful sustenance for all. This also accounts for the rapid depletion of the world’s resources and the concomitant capacity of the environment to regenerate and continue to support human life. This lower-level crisis is often cited as the reason for climate change, erratic climatic events, and other problems of the physical world. The lower-level crisis is related to, even though it is often distinguished from, the upper-level crisis, which though identified as political and economic, is actually a cultural crisis with political and economic manifestations. It is reflected in the basic mental or spiritual disintegration or breakdown of our contemporary materialistic or ‘sensate’ culture and is the direct result of some dysfunction inherent in the very form and dynamics of the human culture (Bidney 1946: 534–7). The situation is such that the assumptions and behaviours that have served humanity for centuries are no longer appropriate and the capabilities that have enabled humanity to attain present levels of civilisation are insufficient to overcome the risks incidental to this achievement. It is this basic cultural crisis that has given rise to the more visible problems of everyday life. Another aspect of the crisis in humanity at this level is related to the tyranny of the marketplace and is manifested in the emergence and growing tendency towards individualism and isolationism. Aristotle wrote in his Politics that man outside the society is either a beast or a god. This essence of humanism is also captured in the African concept and practice of ubuntu, the dictum that ‘I am because we are’; that a person exists because of and through other people. To the contrary, contemporary society seeks to promote the individual over the collective and continues to create new ways of further isolating people from each other. Personal relations have been sacrificed for virtual relationships, which help people relate with one another without the vulnerability that comes with such relationships. Individuals log up thousands of Facebook/ Meta friends who have no existence outside the pages of Facebook/ Meta. Internet and other virtual-world addictions separate individuals from each other even when sharing a common public space. People routinely retreat into the virtual world of iPads, iPods, smart phones, Kindles and tablet computers while out on a date or sharing such communal spaces as public transportation, airport lounges, clubhouses, lecture halls, and doctors’ waiting rooms. Hence, even though the world population is burgeoning and communication gadgets are getting ever more sophisticated by the day, the sense of community continues to atrophy rather than intensify as people relate less with each other and focus more on titillating their own senses, on satiating their own passions, and on seeking individual gratification. The most worrying aspect of the crisis within humanity manifested in the tyranny of passion is the ubiquitous rise of an increasingly common anti-intellectualism. According to Hofstadter (1963: 7), ‘the common thread that binds together the attitudes and ideas called anti-intellectual is a resentment and suspicion of the life of the mind and of those who are considered to represent it; and a disposition constantly to minimize the value of that life’. By this, Hofstadter refers to the current general disdain towards all forms of intellectual activity and a tendency to denigrate those who engage in it, by society in general, and especially by nationalistic ruling classes around the world. Anti-intellectualism has multiple manifestations and, according to Rigney (1991), it is identified with religious anti-rationalism, populist anti-elitism, and unreflective instrumentalism. Religious anti-rationalism refers to the belief in the superiority of faith over reason and the fear that scientific endeavours will lead to the elimination of religion. The growth of religious fundamentalism around the world and the popularity of new-age religions in the face of contemporary life challenges is a testament to this. Indeed, as the humanities crisis deepens, fundamentalist evangelical churches that promise instant miracles continue to prosper and grow in leaps and bounds as adherents flock in, ready and willing to part with their hard-earned meagre resources in the name of planting seeds for the expected miracle of instant material transformation. Populist anti-elitism refers to the notion that academics view themselves as superior to the general population and encompasses, among other traits, ‘a mistrust of claims to superior knowledge or wisdom’ (Rigney 1991: 441). Thus, whereas the dynamics of governing a modern state requires an astute mind with requisite knowledge of people, their communities and the affairs of state, electorates are sometimes said to be more inclined to elect a person with whom they ‘feel comfortable sharing a beer’, or, in democratising countries such as Kenya, the force of affective ties dictate that voters cast their votes to comply with the dictates of ethnic belonging. Paradoxically, such electorates expect their leaders to be adept in economic management, social relations, and political affairs. The third manifestation of anti-intellectualism, unreflective instrumentalism, is said to devalue ‘forms of thought that do not promise relatively immediate practical payoffs’ (McDevitt and Sindorf 2012: 113). The current crisis of the humanities could thus be said to arise from unreflective instrumentalism, especially since the most common critique of the humanities is that it has no relevance in the contemporary neoliberal marketplace. The Demands of the Marketplace and the Worship of Materialism The second level of manifestation of the crisis of humanity is embodied in the demands of the economic marketplace for job-specific qualifications. These demands have an impact on the career choices of fresh university students with the resultant effect of preferring the natural sciences to the humanities. In many parts of the world, Ikpe (2015) contends, university education, including humanities education, had always been seen as a guaranteed way out of undignified manual labour to a life of status, comfort, and privilege. However, over time, this changed as specialisations became narrower and eligibility for specific jobs required having specific qualifications. Since university candidates are either from middle-class or blue-collar backgrounds, it became increasingly important for them to be assured that they were being trained for a specific sector of the labor market as a way of uplifting themselves socially. Whereas this eventuality contributed to growing sophistication of the labour market, it simultaneously undermined, marginalised, and disadvantaged the humanities, particularly courses within the humanities that do not focus on training students for a life within a specific career. Hendry (2004: 3) describes the economic mindset as: rooted in the ideology of market culture and based on the principle of economic self-interest, which privileges private property over the common good and arms-length market over face-to-face interpersonal relationships. This mindset is what has led to universities being required to train rather than educate students. It prioritizes short-term over long-term interests, and treats money as the measure of all good. Features of this economic mindset are increasingly evident in the day-to-day interactions of individuals, communities, and nations. Increasingly, economic considerations are playing a pivotal role in human decisions over and above group interest, morality, and other values. In his epic work on the tyranny of market economics, Sandel observes that ‘we are in the grip of a way of looking at the world and social life and even personal relations that is dominated by economic ways of thinking. That’s an impoverished way of looking at the world’ (Sandel 2012: 194). According to him, the tyranny of market economics has resulted in a consumerist idea of freedom, by which individuals assume that freedom is defined by what they consume. In other words, a person is most free when she or he is capable of consuming whatever it is that she or he desires, whether or not such goods or services are immediately available on the market. Despite acknowledging the role of market economics to world prosperity, Sandel argues that the economic ways of thinking ought not to influence our moral judgement since doing so will limit our freedom to engage in a full civic life. In spite of Sandel’s prescient warning, in the contemporary world, morality appears to be controlled by this economic way of thinking. The world has essentially abandoned the idea of intrinsic rightness or goodness of actions in favour of the instrumental good, with economic considerations as the supreme good of all instrumental actions. Economic considerations determine individual decisions concerning children’s education, fashion, social interactions, religious affiliations, healthcare, transportation, and place of abode, among others. Economic considerations play an important role in the relationship between nations, where multinational corporations, with their considerable economic clout, rule the roost and can make or break the will of individuals, groups, and states. The humanist values of integrity, respect, and compassion only play second fiddle to the values of the neoliberal market. Thus, when humanities scholars complain that their disciplines have been devalued by the demands of the market, they are merely stating what is common to all human processes as they become devalued and subservient to the demands of the market. It is the power of this tyranny of the market that has led to the prevalent culture of worshipping wealth and the wealthy without an iota of care about how such wealth is acquired. Indeed, in contemporary Kenyan society, a person who holds high public office and transitions out without having used the office for self-aggrandisement, such a person is derided and made fun of! Unfortunately, the foundation for this kind of appropriation of public office for self-enrichment was laid by Kenya’s founding president, Jomo Kenyatta. A couple of years after Kenya’s independence when Bildad Kaggia teamed up with the few truly nationalist leaders to fight for the rights of the landless, for social justice and equity in Kenya, and for restructuring Kenya’s colonial economy to work for the ordinary citizens, President Jomo Kenyatta publicly ridiculed him for failing to amass the kind of wealth that his former fellow political prisoners at Kapenguria had amassed for themselves: ‘If you go to Fred Kubai’s home, he has a big house and nice shamba. What have you done for yourself? We were together with Kungu Karumba in prison and now he runs his own business… Kaggia! What have you done for yourself?’ Kenyatta boomed at Kaggia in disgust. Kaggia’s response to this ridicule was emblematic of a true servant-leader with the highest sense of integrity and commitment to the general good. He calmly responded: ‘I was not elected to Parliament to acquire a large farm, a big house or a transport business. My constituents sleep in mud houses. They have no shambas and have no businesses. So, I am not ashamed to be associated with them. By the time they have these things, I will also be able to have them for myself’ (Kamencu 2014: 2). Unfortunately for Kenya, as elsewhere in Africa and even beyond, such leaders of integrity have been rare and far in between. The Mantra of Privatisation and Preoccupation with the Bottom Line The mantra of privatisation and preoccupation with the bottom line is a corollary to the above-elaborated tyranny of market forces. It too, is driven by the spirit and reality of neoliberal economics. Beginning the late-1970s, an insidious neoliberal mindset emerged particularly in Margaret Thatcher’s Britain that encouraged the slow but steady rethinking of the role of higher education away from the notion of a public good towards the idea of privatisation, an idea that Thatcher herself championed. It is, in fact, argued that that she was the first to use the word ‘privatisation’. In Britain, the privatisation project was symbolised by the Buckingham experiment. This was an effort, led by free market devotees like Keith Joseph, to show that the private University College of Buckingham (now the University of Buckingham) could be effective and, more importantly, efficient at delivering a big-ticket item like higher education (Vale 2011 . More than four decades later, Buckingham remains the poster-child for what is approvingly called ‘higher education reform’ through privatisation in Britain and in many parts of the world (Vale 2011: 27–8). This new regime of privatisation with its focus on the economic bottom line saw successive waves of government intervention in the universities. These were spearheaded, especially in Britain, by a network of new higher education authorities who, by invoking the idea of quality and standards, were licensed to conduct audits in the belief that the universities should ‘account’ to the public for the resources they receive from the state. Routines of surveillance, extracted from accounting procedures, were implemented under the idea that they gave greater freedom to students, who were increasingly thought of as consumers or clients. This mantra of privatisation was replicated elsewhere with the establishment of private universities purely for commercial purposes while public universities were increasingly subjected to surveillance to justify continued receipt of public financing. They were increasingly called upon to train for the market rather than educate for humanity. Hence the deemphasis on the humanities and emphasis on the more practical and utilitarian subjects, especially the natural sciences. Funding for the humanities declined while funding for other branches of knowledge, especially in the natural sciences, simultaneously increased because of their presumed guaranteed contribution to the pocketbook. This preoccupation with numeric accounting, with the bottom line, resulted in a regime that enforced ‘performance contracting,’ rated individual academics, and eventually culminated in the ranking of universities. Like much else that drove the idea of globalisation, this was underpinned by the neoliberal belief that it was possible to unite the entire world peacefully in a society of universal commerce (Rothschild 2002: 250). In other words, money has become the only goal in our globalised society. Hence, economics, not state politics nor the morality that the church had preached in earlier ages, would guide the course of human events. In order to survive, the humanities would have to adjust accordingly (Vale 2011: 31). The mantra of privatisation was accelerated by the end of the Cold War and the disintegration of the Soviet Union, which marked the triumph of free market neoliberalism over statist capitalism. Following on from this, the power of individual states found aspects of their sovereignty eroded as business corporations drove the neoliberal agenda towards an increasingly borderless and deeply interconnected world. The resulting condition is the phenomenon called globalisation. The principal beneficiary of the emergence of this globalisation ideology has been the rich individuals, corporations, and countries. This has happened because its underlying principles are driven by the unreflective world of the consumer and in the action world of consumption interests. This turn to the world of practical knowledge and action is rooted in a ‘second nature,’ what Dillon (1994) calls habitus. This second nature resists ‘theorizing or systemizing in terms of abstract ‘underlying principles,’ including those of economic interest’ (Dillon 1994: 211). Reflection of this kind is the great forte of the humanities, which explains why the world of neoliberalism has little place for critical issues like meaning and value, truth and justice, issues which both interest and worry the humanities (Vale 2011: 27). Indeed, in the wake of neoliberal globalisation, the so-called developing countries were called upon to liberalise and privatise, to rationalise and retrench, and to cut back on public spending by eliminating subsidies on staple foods and introducing cost-sharing with consumers of public goods, including education and healthcare. Institutions of higher learning were required to justify continued receipt of public funds by demonstrating their value to the national economy. The impact was decreased funding for disciplines, particularly in the humanities, that could not tangibly demonstrate their contribution to economic development. Many humanities departments in universities were abolished with several disciplines lumped together into single departments, such as history, philosophy, and religious studies. Concomitantly, with public funding constrained, universities resorted to introducing income-generating activities including parallel degree programmes that ended up commercialising public universities and, ipso facto, diluting the essence of university education. Complicit Humanities Scholars At the fourth level of the crisis are the humanities scholars themselves who stand accused of being complicit in the decline of their disciplines as a result of their lack of engagement with society. Ikpe (2015) posits that although it is fashionable to blame outside forces for the decline of the humanities, humanities scholars cannot escape blame for the crisis of their own disciplines. They have not done enough to ensure the continued relevance of their discipline in a fast-changing world (Ikpe 2015: 51). For instance, in lamenting the death of the humanities at Stanford University, Cohn (1994: 60) argued: Though the rise of science, rationalistic secularism, and the political drive to egalitarianism have patently played a part on the mournful drama of the imaginative spirit, for my part, I see no point in faulting science, reason or the idea of fairness, tolerance, justice and decency. The catastrophe, as in individual fate, comes rather with an unhealthy imbalance of the various forces” (Ikpe 2015: 53). Cohn’s position is that although external forces contribute to the decline, other forces, including those arising from the failings of humanities scholars, are as much a part of the equation. One of the most enduring claims is that humanities scholars have, over the years, withdrawn from the wider concerns of society to focus on issues arising within and relevant to the narrow confines of academia. Their views have become so specialised they are no longer intelligible to the general audience which should legitimately benefit from their conversations. Hacker and Dreifus (2010) concur that the link between professors and the public has been severed, largely due to the divorce of academic knowledge from everyday understanding. This view is shared by Lewin (2010: 105) who observes that ‘scholars converse with one another but rarely venture outside the academy to participate in public humanities discussions’. Harpham (2011: 22) similarly asserts that humanities scholars ‘suffer from an inability to convey to those on the outside and even to some on the inside the specific value they offer to public culture’. This disconnect between humanities scholars and the general public has lost them the opportunity of leading opinion on issues that are relevant to contemporary life. Ikpe notes that in limiting conversation about the humanities to an elite club within academia, humanities scholars are probably following the trend in the sciences where the language of science restricts conversations to its inductees. They fail, however, to distinguish between technical communication, which takes place between professionals, and regular communication, which is directed towards the general public. Whereas scientists regularly communicate their ideas to the general public in the form of technological innovations, and as such are not required to speak directly to the public, the ideas emanating from humanities research can only be communicated through direct interaction with society. Cobb (2010: 129) captures the effect of this when he observes that, insisting on ‘pure’ research is keeping professors from other work that would increase their visibility outside academia. Incidentally this attitude has been identified by Frodeman et al. (2003: 30) as similar to the stance of scientists in the early twentieth century when they spoke lovingly of their pursuit of ‘pure’ science: pure because the research was conducted without consideration of use and was motivated by curiosity alone. They argue that this attitude resulted in a poor perception of the sciences until the practical worth of their research was aptly demonstrated during the Second World War. What this shows is that, in concentrating solely on technical communication, without an alternate conversation with society, humanities scholars are alienating the public and emasculating their discipline. Secondly, it is argued that there is a sense in which the study of the humanities has ceased to be interesting, especially to the demographic group that formed its core constituency in years past. Critics observe that the humanities have abandoned the rigorous search for the truth to focus on trivial issues in attempts to accommodate emerging disciplinary interests. Trivial issues such as identity studies, abstruse theory, sexuality, film and popular culture have become part of the mainstream study of the humanities thereby reducing the attention given to traditional humanities curriculum. Whereas I do not agree that the study of identities, sexuality, and popular culture is trivial, I concur with Georg Mann’s exemplification of the extent of triviality in the humanities. Mann (1962: 97) gives an example of cases where ‘moral forces were expended acquiring the skills to riffle through an edition of a sixteenth-century play, note the pattern of typographical errors, and identify not only the print shop but the probable typesetter’. One cannot discount the fact that an exercise of this sort requires skill, but this is not the edifying intellectual exercise that built the humanities and won it respect both within and outside the academy. It however illustrates a growing pattern in humanities research and a tendency for humanities scholars to expend a lot of academic capital in pursuit of the frivolous. It is this growing concern with the trivial that has generated public apathy for the humanities both within and outside the academy. Third, there is also a concern that humanities scholars have shifted their attention away from issues that are the immediate concern of human beings. Wilson (1994: 66) for instance observes that: Philosophy was once written to teach men and women how to live; now, much of it is written to befuddle fellow philosophers. Poems and paintings were once produced to move the spirit and engage the common man; now, many are produced to repel the many and titillate the few. Literature was once thought to convey deep meaning; now, some think it can convey no meaning at all. In other words, the humanities have in the course of history redefined themselves to an extent where they are looked upon as irrelevant by their patrons. Also, in decrying the contemporary direction of arts criticism, Mann (1962: 99) compares a time when criticisms were prepared to improve either the artist’s product or the general public’s understanding to the current situation where criticism has become an end in itself. There is, therefore, a growing consensus both within and outside the academy that humanities discourse has drifted towards the realm of unintelligibility and has stopped being fun both within and outside the academy (Weisbuch 1999: B). Fourth, the humanities have also been accused of not being sufficiently innovative in a world that is constantly evolving. While there is nothing wrong with studying the Homeric poems or investigating the impact of the trans-Saharan trade on the great empires of West Africa, it would be foolhardy to expect this to be of interest to the society if members of the public cannot relate it to contemporary life. Humanities knowledge appears to have become stale and no effort has been made by scholars to inject a new relevance to it. The story is told of the president of a major research university, who when he offered his faculty members funds for new proposals, received more than 50 ideas from scientists, 30 from social scientists, and nothing from humanists except requests to put more money into existing programmes (Weisbuch 1999: B4). In other words, humanities scholars are not sufficiently innovative but rather hide under the same tired old research programmes that they inherited from their mentors. They do not open up new research trends for their students and end up cloning themselves professionally and presiding over a creeping homogeneity (Cobb 2010: 128) within academia. Even where there is innovation, the direction of such innovation sometimes leaves observers more perplexed as it sometimes entails what Deneen (2010: 60) refers to as victimisation studies, namely multiculturalism, disability studies, queer studies, and so on, studies that do not define a holistic human experience but highlight the past in a way that is not useful for the future. In all, the humanities have been accused of either being trapped in the past or wandering aimlessly in the wilderness of the future. Toward Recuperation: The Significance of the Humanities Despite the foregoing crisis, the humanities confront issues of great political significance and do so typically in ways that cut beneath specific policy questions. Recognising differences in the humanities disciplines with regard to content and method, Martha Nussbaum (2002) argues that all of this diversity is held together by a set of themes and problems: roughly, the problem of how to live with dignity as a rational animal, in a world of events that we do not fully control. Issues of human vulnerability and need, of terror and cruelty, also of pleasure and vision, are its subject matter, a subject matter as capacious as life itself, but pursued with a reflectiveness and rigor that life itself rarely attains (Nussbaum, 2002: 39). In real life, Nussbaum contends, people typically seek to avoid the challenge that the humanities pause: they live unreflective lives, lives that are often cramped and narrowed by the pursuit of gain, or bare security, lives in which the imagination of human suffering is frequently allowed to lapse if, indeed, it ever existed. According to her, If we want only one reason why the humanities are essential in public life in this era of rapid globalization, a sufficient such reason is that the humanities keep our eyes on the human meaning of public policy and on a rich human and ethical set of ends for human action, while economic science too easily narrows its vision, lending itself as a tool to the forces that already are committed to the all-out pursuit of profit. This means that the humanities … are key to dispelling barriers of hatred and ignorance that divide people the world over by class, caste, race, sex, and religion and thus key to the formation of just sets of policies in the area of human development… (Nussbaum, 2002: 39–40). According to Patricia Spacks (2006), successive revolutions during the past century have energised the natural sciences in often thrilling ways. Given the evidence for dramatic change apparent in new discoveries, new inventions, and new solutions to recognisable problems, the educated public understands that recurrent transformations only corroborate the importance of the natural sciences as an intellectual endeavour. Corresponding transmutations of the humanities, in contrast, prove both less recognisable and less readily acceptable, not only to the public, but even to academics professing the natural sciences and the social sciences. Nevertheless, seismic shifts have altered individual disciplines in the humanities in the course of the twentieth century. Such alterations generate no new understanding of the brain or the biosphere, but they can change our ways of comprehending our cultural heritage and thus our grasp of what it means to live in the world – a shift of consciousness potentially as consequential as mapping the human genome. Kant argues convincingly that a robust critical public culture, prepared to question authority in the name of morality, rests on a respect for reason and its constraint (cited in Nussbaum 2002: 42). Yet, the illumination and human understanding that the humanities have given in this regard, and are still giving, to our undergraduates and our culture, may gradually be lost. When administrators, parents, and students focus narrowly on the bottom line, it is difficult to see the relevance of literature and philosophy. They look like useless frills, distractions from the real business of education, which is all too often seen as preparation for a job. This utilitarian approach to the humanities, Nussbaum notes, did enormous damage in Thatcher’s Britain, where universities were asked to justify their humanistic pursuits by showing that they contributed to economic growth. A fundamental thing that needs underscoring is that college education is a general preparation for citizenship and for life, and a formation of citizens for our public culture. It is not difficult to see that the humanities provide essential ingredients for citizenship: clarity of mind, knowledge of the world, an expansive and subtle imagination. Indeed, universities exist to serve the general public rather than the narrow interests of capitalist entrepreneurs. As the 1963 Robbins Report on Higher Education in the United Kingdom points out, universities are charged with four main functions of which instruction in skills is only one. The other three are the search for truth (hence the importance of academic freedom), the transmission of a common culture and common standards of citizenship, and, perhaps most importantly, the promotion of the general powers of the mind in order to produce cultivated men and women rather than mere specialists for the labour market (Nasong’o 2018). And herein lies the significance of the humanities. A public policy made without the influence of the humanities is likely to be a cramped and crude policy (Nussbaum (2002: 48). The cultivation of the imagination that comes with the study of literature, the cultivation of the ethical sensibility that comes with the study of philosophy and religion, these are essential equipment for citizens and policy makers in a world increasingly united, and driven forward, by the profit motive. The capacity to look at a single life with understanding and love is not automatic, and can also be lost. We need to think clearly about this danger, and try as best as we can to prevent it, through strong support for the future of these disciplines. Hence, artists and humanists, who seek out the common pleasures and visions, the terrors and cruelties of an individual’s day on this planet, are people of great political significance, even and especially when what they do is not simply about politics. It is difficult to see how we can have any hope of overcoming barriers of prejudice and ignorance without them. So, in view of the imperative significance of the humanities, what can be done to address the crisis that confront these disciplines? A number of remedies can be gleaned from extant literature on the subject. First, the wealth of knowledge within the humanities needs to be harnessed for practical use through such a reinvention as happened in ethics towards the end of the twentieth century. During the final quarter of the twentieth century, a combination of scientists and philosophers brought ethics down from the clouds of meta-ethical abstraction to dwell among the scientific clinics, research laboratories, industrial applications, and technological communications networks. The emergence of biomedical ethics, research ethics, environmental ethics, and computer ethics is an attempt by the humanities to help humanity live appropriately with the expanding powers of science and technology (Frodeman et al. 2003: 31). The second remedy should entail humanities scholars reengaging more assertively with the general public with a view to reasserting the rule of reason over the tyranny of passion and, in so doing, return the humanities to humanity. Humanities scholars should increase the role of the humanities disciplines beyond the academy by sensitising the general public to the vital role that the humanities can and does play in fostering a critical civil society. In this vein one can argue following Harpham (2011: 152) that a study of the humanities leads to ‘an awakened understanding of oneself as a member of the human species, a heightened alertness to the possibilities of being human’ and also the capacity to sympathise, empathise, or otherwise inhabit the experiences of others. One can also argue like Nussbaum (1997: 8) that the humanities ‘liberates the mind from the bondage of habit and custom, producing people who can function with sensitivity and alertness as citizens of the whole world’. A third way of saving the humanities should involve projecting the value of humanities education to the public and convincing them of the role that the humanities play in contemporary life. In extolling the value of the humanities in academic medicine, for instance, Fins et al. (2013: 355) argue that philosophy, history, literature, and the arts already offer a discourse instrumental to reflective practice. These disciplines encourage introspection and a deeper understanding of how medicine operates within society. Such reflection has a ‘transformative power’, enabling practitioners to, in John Dewey’s words, ‘reconstruct’ the world. They further argue: Even though science is the bedrock of medicine, science does not fully capture the personal dimension of clinical work. The practice of medicine becomes art and ceases to be, in the words of Karl Popper, falsifiable... The scientific realm limits and constrains a broader practice of medicine because it excludes other ways of knowing that cannot be ascertained, explored, or probed by the notion of falsifiability. If one were to remove those other ways of knowing, it would impoverish medical practice and deny patients the humane care that they want and deserve. (Fins et al. 2013: 360). Lata and Devika (2013: 333) make a similar argument concerning humanities and engineering when they argue that ‘arts and humanities courses inculcate creative thinking which is indispensable to explore creative and analytical techniques for generating fresh ideas and possibilities and select an appropriate solution or take an implementable decision’. Similarly, in outlining the importance of the humanities for business executives, Joseph Pichler (1983: 13) notes that Business courses have a comparative advantage in teaching future executives to develop systems of evaluation, execution, and control. The humanities have an advantage in developing a predisposition for creative and integrative thinking. These qualities of mind are more likely to be instilled if the humanities are taught from a humanistic rather than a technical perspective. In the same vein, in discussing the humanities’ unique contributions to society, Chambers (2001: 4) argues that ‘typically moral dilemmas (concerning euthanasia, unemployment, genetic modification and so forth) all involve questions of value which is the particular concern of the humanities’. What this suggests, Chambers posits, is that scholars of the humanities are not merely teaching techniques of doing things which, once studied, can be applied to an appropriate trade within society. They are, rather, cultivating an inquiring mind that ought to be able to grapple with the fundamental problems of society and proffer innovative solutions that transcend knowledge acquired in the classroom (McCormick 2001). The fourth remedy is the need to reassert the idea of humanities as therapy. In this regard, humanities therapy should seek to harness its therapeutic value not only because it is necessary for its own survival as an academic discipline, but also because of the practical benefits that accrue for humanity. Humanities therapy may be defined as the theoretical and practical activities that prevent and cure mental and emotional problems (Keon-Sang 2012). It is more readily recognised by its popular and practical variant, creative or expressive arts therapy. Creative-arts therapy consists in the use of music, painting, clay, dance, voice or drama for therapeutic purposes under the direction of a therapist. It is this therapeutic function of the humanities that Hudson-Jones (1997: 275) refers to when she argues, The physician and the poet can both be healers. They share a common goal in their efforts to maintain light and order against the chaos of darkness and disease, and to create or restore the beauty and harmony of health: in this quest, medicine serves the body, poetry the spirit. The notion of humanities as therapy dates back to biblical times in the relationship between David and Saul and has been growing ever since. According to the Bible, ‘whenever the tormenting spirit from God troubled Saul, David would play the harp. Then Saul would feel better, and the tormenting spirit would go away’ (1 Samuel 16: 23). Poetry readings, for instance, can soothe the minds of those brutalised by the tyranny of the economic mindset, while selected literary readings can help humanity to discover that there are values that do not have a price tag. The Socratic method of philosophical counselling can help people discover the truth about themselves and their environment and the general appreciation of culture can stem the social and moral decay that results in disillusionment, discontent and disaffection. A humanistic therapy for the sane is indeed what humanity needs, not only to help it appreciate the humanities but, more importantly, to help it rediscover itself (see Ikpe 2015: 51). Fifth, it is imperative for humanities scholars to demonstrate that it is only their disciplines that can help redress the crisis of humanity especially as embodied in the tyranny of the market and the tyranny of passion. This is because only the humanities are concerned with the development of human consciousness or the transcendence of the human condition (Gastile 1977: 10). It is therefore up to the scholars of the humanities to convince a sceptical public of their capacity to make a difference within the current crisis. One way of doing so, according to Mann (1962: 98), is for the humanities scholar (the practitioner of humanities) to double up as a humanist. In Mann’s view, a humanist is one who uses facts, while a practitioner of the humanities is merely one who discovers them. For a long time, humanities scholars have been primarily concerned with the search for facts within their disciplines and have lost out on the opportunity to use such facts in the service of humanity. The idea of learning for its own sake has been highly prized, while the relevance of such learning to the immediate challenges of culture has been ignored. For Mann therefore, the humanities disciplines can only regain their pride of place in academia when the humanities scholars either become humanists or at least make contributions toward humanism. Currently, ‘the professional study of literature, the languages, philosophy, the fine arts and history by competent scholars of the humanities, is not necessarily either humane nor a contribution to humanism’ (Mann 1962: 99). This has to change for the public perception of the humanities to change. The humanities need to abandon the idea of the university as an ivory tower and appreciate the fact that the production and dissemination of knowledge is not limited to the classroom, but also be achieved through an engagement with society. It is through such engagement that the public will come to realise that not all items of value are exchangeable commodities with a price tag. Sixth and finally, it is even more critical to make the argument that the humanities do teach people a lot of vocational skills and that the creativity, flexibility, and adaptability of people trained in the humanities are in demand where employers need to employ people with facility in critical thinking and who can cope with change and uncertainty (Viljoen 2008: 9). Making these arguments, as Viljoen (2008) observes, may appear as succumbing to the tyranny of the market and an endorsement of the ‘unreflective instrumentalism’ that have been elaborated above as the bane of contemporary society. But, Viljoen rightly adds, there is need to ‘stoop to conquer’ and in doing so save the humanities from total extinction. Conclusion This paper has explored the crisis in the humanities and traced its development across the space of time. It has explored the causes of the crisis and strongly demonstrated that the crisis in the humanities is indeed a manifestation of a deep crisis in humanity more generally. The crisis of humanity, the paper shows, is manifested in the tyranny of passion or the rule of the senses over reason, the demands of market forces and the worship of materialism, the neoliberal mantra of privatisation and preoccupation with the bottom line, and complicit humanities scholars who have divorced academic knowledge from everyday realities and understandings by increasingly conversing with one another but rarely venturing outside the academy to participate in public humanities discourses. This disconnect between humanities scholars and the general public has lost these scholars the opportunity of leading opinion on topical issues of great significance to contemporary life. The paper has articulated a number of measures to help redress the crisis in the humanities. These include harnessing the wealth of knowledge within the humanities for practical use, reengaging more assertively with the public with a view to reasserting the rule of reason over the tyranny of passion and the greed of markets, projecting to the public the critical value of a humanities education, and reasserting the age-old idea of humanities as therapy, among others. Overall, humanities scholars need to engage more with society even as they continue in scholarly activities that have defined the humanities through the ages. A reassertion of humanities therapy in all its expressive trajectories is a critical way for the humanities disciplines to engage with the contemporary world that is increasingly enamoured with the world of technology even though the vast majority of humans are technological immigrants rather than technological natives.